Smallholder Farmers Climate-Smart Crop Diversification Cost Structure: Empirical Evidence From Western Kenya - Awiti, Hezbon Akelo; Gido, Eric Obedy; Obare, Gideon Aiko (Frontiers in Sustainable Food Systems, 2022)
Climate-smart agriculture (CSA) is increasingly becoming important as a sustainable way of increasing agricultural productivity and increasing the resilience of farming systems to climate variability. Moreover, crop diversification strategy plays a vital role in creating resilience against climate-related risks in farm production and enhancing resilience in food systems. While crop diversification intensity acts as a proxy indication of climate risk mitigation strategy, its successful implementation as a climate-smart agricultural practice depends on the ability of the smallholder farmers to allocate the available farm resources efficiently. The study evaluated the effect of crop diversification on variable cost structure (land, labor, capital, fertilizer, and seeds) among smallholder farmers in Western Kenya. We use primary data from 267 randomly selected respondents and apply a translog cost function model to explore the effect of implementing crop diversification strategy on variable cost structure among smallholder farmers. The results showed that indeed practicing crop diversification affects the overall production cost structure. The result showed that the Allen elasticity of substitution (AES) of all combinations of inputs (land and capital, land and fertilizer, land and labor, fertilizer and capital, fertilizer and labor, fertilizer and capital) are positive. These relationships imply that land, labor, fertilizer, and capital substitute each other in crop production. The Morishima elasticities of factor substitution (MES) reveal that the highest degree of substitutability in response to price changes is between capital and fertilizer, land and fertilizer, and labor and fertilizer, implying the intensive nature of crop diversity in terms of land, labor and capital requirements. These findings demonstrate that despite the potential benefits of crop diversification, the trade-off in the total cost of production does matter. Non-accounting for such trade-offs is likely to over-estimate crop diversification benefits and limit its successful practice by smallholder farmers.